Luteolin promotes apoptotic cell death via upregulation of Nrf2 expression by DNA demethylase and the interaction of Nrf2 with p53 in human colon cancer cells - Kang, Kyoung Ah (Exp Mol Med, 2019)
Luteolin, a dietary flavone, modulates various signaling pathways involved in carcinogenesis. In this study, we investigated the molecular mechanism that underlies the apoptotic effects of luteolin mediated by DNA demethylation of the nuclear factor erythroid 2-related factor 2 (Nrf2) promoter and the interaction of Nrf2 and p53, a tumor suppressor, in human colon cancer cells. Luteolin increased the expression of apoptosis-related proteins and antioxidant enzymes. In DNA methylation, luteolin inhibited the expression of DNA methyltransferases, a transcription repressor, and increased the expression and activity of ten-eleven translocation (TET) DNA demethylases, a transcription activator. Methyl-specific polymerase chain reaction and bisulfite genomic sequencing indicated that luteolin decreased the methylation of the Nrf2 promoter region, which corresponded to the increased mRNA expression of Nrf2. In addition, luteolin increased TET1 binding to the Nrf2 promoter, as determined using a chromatin immunoprecipitation (ChIP) assay. TET1 knockdown decreased the percentages of luteolin-treated cells in sub-G(1) phase and cells with fragmented nuclei. Furthermore, complex formation between p53 and Nrf2 was involved in the apoptotic effects of luteolin. These results provide insight into the mechanism that underlies the anticancer effects of luteolin on colon cancer, which involve the upregulation of Nrf2 and its interaction with the tumor suppressor.